2009
DOI: 10.1097/01.aids.0000363777.76129.b4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of contraceptive choice among women with HIV

Abstract: Among HIV-infected women, several characteristics that may place women at greater risk for unintended pregnancy and its adverse consequences were associated with choice of highly effective contraceptive methods. These findings may aid in the development of interventions to increase use of effective contraception among HIV-infected women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 22 publications
4
17
0
2
Order By: Relevance
“…A oferta de novas opções contraceptivas, por exemplo, os métodos reversíveis de longa duração (LARC), poderá colaborar para o aumento da adesão e eficácia contraceptivas nessa população, assim como ocorre na população geral [33][34][35] . A resistência do parceiro em usar condom foi um preditor, com chance três vezes maior de má adesão à dupla contracepção e o desconhecimento do parceiro quanto à condição da mulher ser soropositiva para o HIV como determinante de maior adesão com chance quase que duas vezes maior de aderir à dupla contracepção.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A oferta de novas opções contraceptivas, por exemplo, os métodos reversíveis de longa duração (LARC), poderá colaborar para o aumento da adesão e eficácia contraceptivas nessa população, assim como ocorre na população geral [33][34][35] . A resistência do parceiro em usar condom foi um preditor, com chance três vezes maior de má adesão à dupla contracepção e o desconhecimento do parceiro quanto à condição da mulher ser soropositiva para o HIV como determinante de maior adesão com chance quase que duas vezes maior de aderir à dupla contracepção.…”
Section: Discussionunclassified
“…METHODS: A cross-sectional study carried out from December 2013 to September 2014 at a local reference center, with application of questionnaire elaborated after Delphi panel and content validation to 114 HIV(+) women aged 15 to 49 years, using DMPA plus condom for contraception. RESULTS: Mean age was 33 …”
Section: Purposementioning
confidence: 99%
“…Globally, DMPA is most commonly used hormonal contraceptive among HIV positive women, and has been show to more effectively prevent unplanned pregnancies among HIV serodiscordant couples than combined oral contraceptive pills [13,21]. Combined Oral Contraceptive pills (COC) are the most commonly used method of contraception among U.S. adolescents, they are used by 22% of adolescents and 56% of contraceptors in this age group [15,22].…”
Section: Discussionmentioning
confidence: 99%
“…HIV infected adolescents reported prior use of dual protection during 16% of their visits [4]. Previous international studies have demonstrated that HIV positive adolescent and adult women are more likely to request injectable contraceptives than their HIV negative peers [4,9,[11][12][13]. Risk of HIV acquisition or progression among hormonal contraception users has been a recent concern based on international trials [14].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23] However, UNAIDS has noted that unintended pregnancy rates among HIV-positive women range from 51% to 90% in reported research. 24 HIV-positive women's motivations for terminating pregnancies partly coincide with those of other women: the pregnancy resulted from rape or incest; 25 they did not use or were prevented from using contraception, or their method failed, but they did not want a(nother) child; 26 the pregnancy occurred too soon after their last childbirth; 26 they did not want to bring a child into an abusive relationship; 27 they were not in a steady relationship and could not cope alone; they did not have sufficient socioeconomic resources to care for the child;…”
Section: Reasons For Abortion Among Women Living With Hivmentioning
confidence: 99%